Inequalities in the care experiences of patients with cancer: analysis of data from the National Cancer Patient Experience Survey 2011–2012. Issue 2 (14th February 2014) - Bone, Anna; Mc Grath-Lone, Louise; Day, Sophie; Ward, Helen
Abstract : Objectives: To explore inequalities in the care experiences of care by patients clinical or trust-level factors for patients with cancer. Design: Secondary analysis of data from the National Cancer Patient Experience Survey 2011–2012. Setting and participants: Adult patients with a primary diagnosis of cancer who attended an acute or specialist National Health Service (NHS) trust in England. Outcome measure: OR of a patient rating their overall care positively, adjusting for other patient, clinical and trust-level factors. Methods: Using cross-sectional data from 71 793 patients with cancer who completed the National Cancer Patient Experience Survey 2011–2012, we examined associations between patient, clinical and trust-level factors and a summary measure of patient experience, namely overall rating of care. Multivariate logistic regression was used to investigate variation by sociodemographic characteristics adjusting for other patient, clinical and trust-level factors. Results: Female, non-white and younger patients were less likely to rate their overall care as excellent or very good. Patients with long-standing conditions, particularly those with learning disabilities or mental health conditions, also reported poorer overall care. This variation persisted when other patient, clinical and trust-level factors were controlled for, indicating that there are real differences in experiences among patients with cancer by sociodemographic characteristics. Conclusions: There is evidence of inequalities in the experiences of patients with cancer in the UK by sociodemographic characteristics such as gender, age, ethnicity and disability. Quality cancer care services must strive to meet the needs of a diverse patient population equally; this study identifies patient groups for whom it appears cancer care services are in greatest need of improvement.